Real‐Time Fluorescent Monitoring of Kinetically Controlled Supramolecular Self‐Assembly of Atom‐Precise Cu8 Nanocluster. (16th March 2022) - Sun, Pan‐Pan; Han, Bao‐Liang; Li, Hong‐Guang; Zhang, Cheng‐Kai; Xin, Xia; Dou, Jian‐Min; Gao, Zhi‐Yong; Sun, Di
Abstract: Kinetically stable and long‐lived intermediates are crucial in monitoring the progress and understanding of supramolecular self‐assembly of diverse aggregated structures with collective functions. Herein, the complex dynamics of an atomically precise Cu I nanocluster [Cu8 ( t BuC6 H4 S)8 (PPh3 )4 ] (Cu8a ) is systematically investigated. Remarkably, by monitoring the aggregation‐induced emission (AIE) and electron microscopy of the kinetically stable intermediates in real time, the directed self‐assembly (DSA) process of Cu8a is deduced. The polymorphism and different emission properties of Cu NCs aggregates were successfully captured, allowing the structure–optical property relationship to be established. More importantly, the utilization of a mathematical "permutation and combination" ideology by introducing a heterogeneous luminescent agent of a carbon dot (CD ) to Cu8a aggregates enriches the "visualization" fluorescence window, which offers great potential in real time application for optical sensing of materials. Abstract : Within the scheme of aggregation‐induced emission (AIE), optical‐engineering was performed for real‐time monitoring of the self‐assembly process of Cu8a with various kinetic long‐lived intermediates, leading to a structure–property relationship being established.